PERCEPTION AND INTERPRETATION OF THE NEW ISSUE MARKET AMONG RETAIL INVESTORS- A THEMATIC REVIEW - Agarwal, Eti; Srivastava, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Higher participation of retail investors in the New Issue Market (NIM), specifically of Initial Public Offerings (IPOs), has been causing concern regarding the extent of financial literacy and well-informed decision-making expected of them. The current review paper critically analyzes the financial literacy of retail investors in the context of the NIM, specifically their comprehension of benefits, risks, regulatory protection, and common myths. While IPOs are typically high-return investments, retail investors as a whole undergo the process without much knowledge of the processes involved, e.g., pricing mechanisms, allocation procedures, and disclosure mandates. Such surface-level knowledge will typically lead to unrealistic suppositions and a higher susceptibility to market speculative and hype situations. The research also addresses popular misconceptions in IPO investment — that every IPO is profitable or that an oversubscription is a sign of quality — and examines the impact on the behavior of investors. The article also points out the useful role of the Securities and Exchange Board of India (SEBI) towards investor education, bringing transparency, and practicing regulation through regulatory protective mandatory disclosures like the Red Herring Prospectus and warning investors against risk. Drawing on secondary data and thematic synthesis of the literature, the paper highlights the necessity for focused financial literacy interventions in bridging the gap between awareness and in-depth understanding of the NIM among retail investors.